2018
DOI: 10.1109/lwc.2018.2797904
|View full text |Cite
|
Sign up to set email alerts
|

On Channel Hopping Sequences With Full Rendezvous Diversity for Cognitive Radio Networks

Abstract: In cognitive radio networks (CRNs), establishing a communication link between a pair of secondary users (SUs) requires them to rendezvous on a common channel which is not occupied by primary users (PUs). Under time-varying PU traffic, asynchronous sequence-based channel hopping (CH) with the maximal rendezvous diversity is a representative technique to guarantee an upper bounded time-torendezvous (TTR) for delay-sensitive services in CRNs, without requiring global clock synchronization.Maximum TTR (MTTR) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Meanwhile, the sender plays the role of “child” which stays at the same channel for L time slots to be found by the receiver and then repeatedly hops to another unvisited channel. The FARCH [30] is another GC scheme which follows similar procedures as the WFM for generating its CH sequences when L is even. However, the FARCH receiver follows a different strategy when L is odd which enhances the TTR performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the sender plays the role of “child” which stays at the same channel for L time slots to be found by the receiver and then repeatedly hops to another unvisited channel. The FARCH [30] is another GC scheme which follows similar procedures as the WFM for generating its CH sequences when L is even. However, the FARCH receiver follows a different strategy when L is odd which enhances the TTR performance.…”
Section: Related Workmentioning
confidence: 99%
“…This section presents the performance evaluation of the developed QS-CH and IQSF-CH schemes as compared with some extant blind CH rendezvous schemes. The proposed QS-CH scheme is compared with six representative asymmetric-role schemes (four GC schemes, FDCH-RP [27], PCH [28], AAsync [31], and FARCH [30,34] as well as two LC schemes named as D-QCH in [32] and SJRW [23]). On the other side, the proposed IQSF-CH scheme is compared with six representative symmetric-role CH schemes (four GC schemes, EJS [20], T-CH [40], D-CH [40], and S-QCH in [32] as well as two LC schemes named as ZOS [44] and MTP [21,43]).…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Non-assisted rendezvous, on the other hand, is one that operates without the assistance of a central controller (or another node) and does not have a CCC. There are many approaches for non-assisted rendezvous techniques presented in the conventional references [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The general terminologies used for our articles related to rendezvous are summarized as follows: Channel Symmetricity : For the symmetric channel, the cognitive radio transmitter (CR-Tx) and cognitive radio receiver (CR-Rx) have the same available channels.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the uncertainty of channel symmetry and time synchronization at either end of CR nodes, a universal algorithm is needed for further improvement. A deterministic succession-based rendezvous for a better outcome was analysed in [ 26 ] and they proposed a channel rendezvous with maximum diversity. Bian et al suggested an asynchronous channel-hopping scheme [ 27 ].…”
Section: Introductionmentioning
confidence: 99%